Identification of Shared and Unique Serum Lipid Profiles in Diabetes Mellitus and Myocardial Infarction. Issue 12 (29th November 2016) - Kjellqvist, Sanela; Klose, Christian; Surma, Michal A.; Hindy, George; Mollet, Inês G.; Johansson, Anna; Chavaux, Patrick; Gottfries, Johan; Simons, Kai; Melander, Olle; Fernandez, Céline
Abstract : Background: Diabetes mellitus (DM) and cardiovascular disease are associated with dyslipidemia, but the detailed lipid molecular pattern in both diseases remains unknown. Methods and Results: We used shotgun mass spectrometry to determine serum levels of 255 molecular lipids in 316 controls, 171 DM, and 99 myocardial infarction (MI) events from a cohort derived from the Malmö Diet and Cancer study. Orthogonal projections to latent structures analyses were conducted between the lipids and clinical parameters describing DM or MI. Fatty acid desaturases (FADS) and elongation of very long chain fatty acid protein 5 (ELOVL5) activities were estimated by calculating product to precursor ratios of polyunsaturated fatty acids in complex lipids. FADS genotypes encoding these desaturases were then tested for association with lipid levels and ratios. Differences in the levels of lipids belonging to the phosphatidylcholine and triacylglyceride (TAG) classes contributed the most to separating DM from controls. TAGs also played a dominating role in discriminating MI from controls. Levels of C18:2 fatty acids in complex lipids were lower both in DM and MI versus controls (DM, P =0.004; MI, P =6.0E‐06) at least due to an acceleration in the metabolic flux from C18:2 to C20:4 (eg, increased estimated ELOVL5: DM, P =0.02; MI, P =0.04, and combined elongase‐desaturase activities: DM, P =3.0E‐06; MI, P =2.0E‐06). Minor allele carriers of FADS genotypes were associated with increased levels of C18:2 ( P ≤0.007) and lower desaturase activity ( P ≤0.002). Conclusions: We demonstrate a possible relationship between decreased levels of C18:2 in complex lipids and DM or MI. We thereby highlight the importance of molecular lipids in the pathogenesis of both diseases.